Representation of Sexual Harassment Victims in English-based Indonesian Online News: A Critical Discourse Analysis - Hibatulloh, Muhammad Firnas; Rasyid, Fathor (UIII Press, 2024)
This study aims to investigate representations of sexual harassment victims in English-based Indonesian online news and reveal the underlying ideology behind the representation. This study uses critical discourse analysis with Fairclough’s framework. Halliday’s systemic functional grammar is applied in terms of the transitivity process. Data were news articles published in Tempo.co, The Jakarta Post and Antara. The data were analyzed using Eggins’ transitivity analysis keywords and then classified based on the transitivity process. The result shows that there are 88 transitivity processes consisting of 44 material processes, 26 verbal, ten relational attributive, one relational identifying, four mental and three existential processes. The behavioral process is not found in news articles. All English-based Indonesian online news represents sexual harassment victims positively. All news agencies represent that sexual harassment cases are not handled properly. This representation shows that all online news agencies support the ideology of gender equality and feminism at a varied rate. Tempo.co are less clear in showing their partiality. The news agencies are clear enough in showing their partiality to the sexual harassment victim. However, all of the online news agencies still represent the victim as a powerless object towards the perpetrator’s actions. However, there are misjudgments about the victim presented by The Jakarta Post and misrepresentation represented by Tempo.co and Antara. This implies that English-based Indonesian online news agencies still contain a patriarchal culture in their news reports.